Language learning for specific purposes (LSP) in technical education: addressing unique language needs - Kochergina, S. S.; Khoroshailo, O. S.; Кочергіна, С. С.; Хорошайло, О. С. (ТОВ «УКРЛОГОС Груп», 2024)
In this paper, we discuss the importance of Language for Specific Purposes (LSP) in higher technical education, highlight the unique language needs of these students, and argue that addressing these needs can significantly enhance their learning experience.The English language skills needed by these students differ significantly from those required by students of other disciplines. Technical students must be able to comprehend and communicate complex concepts related to their field of study. They need to understand specialized terminology, technical jargon, and academic discourse that is specific to their area of interest.
Keywords: Language for Specific Purposes; higher technical education; students